Macroeconomics : individual choice and its consequences - Skaggs, Neil T.; Dillingham, Alan E.; Carlson, J. Lon. (Cambridge, Mass. : Blackwell, 1996)
This book contains key concepts and graphs, key terms, fill-in-the-blank and graphing problems, multiple choice questions, and an answer key with explanations for the problems and questions
Rev. ed. of the "Macroeconomics" section of: Economics / Alan E. Dillingham. c1992.
Includes bibliographical references and index.
gau 03/02/14
Loans
Keywords: Macroeconomics